"At the End We Feel Forgotten": Needs, Concerns, and Advice from Blogs of Dementia Family Caregivers. (January 2021) - McLennon, Susan M.; Davis, Altheria; Covington, Sarah; Anderson, Joel G.
Illness blogs have been used by many individuals to describe their experiences, share knowledge, and gather support. The purpose of this study was to identify needs, concerns, and advice from the blogs of caregivers caring for a person with dementia at the end of life (EOL). A qualitative thematic analysis was performed of 192 blog postings from six dementia family caregivers during the EOL. A Google search using a systematic identification method was followed. Caregivers were females caring for mothers ( n = 5) and husbands ( n = 1). Themes varied by EOL stage within the contextual environment of Grief/Loss, Family, and Spirituality. Pre-death themes were Care Transitions and Quality; dying were Physical and Emotional Aspects; and post-death were Relief and Remembering. Four additional themes transitioned across stages: Decision-Making, Health Care Providers, Advice, and Caregiver Support. Findings suggest caregiver needs, concerns, and advice vary by EOL stage. Implications for tailored interventions should be considered.